Application of a Thermo-Reversible Gelation Polymer, Mebiol Gel, for Stem Cell Culture and Regenerative Medicine - Kataoka, K (Journal of Stem cells and Regenerative medicine, 2010)
Recent studies have revealed the possible utility of a three-dimensional culture system using a thermo-reversible gelation polymer, Mebiol Gel. It is a purely synthesized biocompatible copolymer composed of thermoresponsive polymer blocks [poly(N-isopropylacrylamide-co-n-butyl methacrylate) poly(NIPAAm-co-BMA)] and hydrophilic polymer blocks (polyethylene glycol [PEG]). Mebiol Gel is characterized by its temperature-dependent dynamic visccoelastic properties. Mebiol Gel is used as a biocompatible scaffold for three-dimensional culture without any toxicity. Representative biological scaffolds for three-dimensional culture, i.e. type I collagen and Matrigel, interact with cells and affect cellular functions, but Mebiol Gel hardly showed such effects. Because of its innertness, Mebiol Gel enables clonal expansion of single stem cells. Application of Mebiol Gel to tissue defects in animal models revealed that Mebiol Gel enhanced tissue regeneration with activation of stem cells and prevention of inflammation. Thus, Mebiol Gel is suitable for preparation of cells for transplantation and is useful for direct application to promote regeneration of damaged tissues in vivo.